Use of Nanostructured Silica SBA-15 as an Oral Vaccine Adjuvant to Control Mycoplasma hyopneumoniae in Swine Production - Storino, Gabriel Y. [UNESP]; Petri, Fernando A. M. [UNESP]; Mechler-Dreibi, Marina L. [UNESP]; Aguiar, Gabriel A. [UNESP]; Toledo, Leonardo T.; Arruda, Laíza P. [UNESP]; Malcher, Clarisse S. [UNESP]; Martins, Tereza S.; Montassier, Hélio J. [UNESP]; Sant’Anna, Osvaldo A.; Fantini, Márcia C. A.; de Oliveira, Luís Guilherme [UNESP] (My University, 2023)
Mycoplasma hyopneumoniae is a difficult-to-control bacterium since commercial vaccines do not prevent colonization and excretion. The present study aimed to evaluate the performance of an orally administered vaccine composed of antigens extracted from Mycoplasma hyopneumoniae and incorporated into mesoporous silica (SBA-15), which has an adjuvant-carrier function, aiming to potentiate the action of the commercial intramuscular vaccine. A total of 60 piglets were divided into four groups (n = 15) submitted to different vaccination protocols as follows, Group 1: oral SBA15 + commercial vaccine at 24 days after weaning, G2: oral vaccine on the third day of life + vaccine commercial vaccine at 24 days, G3: commercial vaccine at 24 days, and G4: commercial vaccine + oral vaccine at 24 days. On the first day, the piglets were weighed and, from the third day onwards, submitted to blood collections for the detection and quantification of anti-Mycoplasma hyopneumoniae IgG. Nasal swabs were collected to monitor IgA by ELISA, and oropharyngeal swabs were used to assess the bacterial load by qPCR. Biological samples were collected periodically from the third day of life until the 73rd day. At 41 days of life, 15 individuals of the same age, experimentally challenged with an inoculum containing M. hyopneumoniae, were co-housed with the animals from groups (1 to 4) in a single pen to increase the infection pressure during the nursery period. At 73 days, all piglets were euthanized, and lungs were evaluated by collecting samples for estimation of bacterial load by qPCR. Quantitative data obtained from physical parameters and laboratory investigation were analyzed by performing parametric or non-parametric statistical tests. Results indicate that animals from G2 showed smaller affected lung areas compared to G3. Animals from G2 and G4 had a low prevalence of animals shedding M. hyopneumoniae at 61 days of age. Additionally, no correlation was observed between lung lesions and M. hyopneumoniae load in lung and BALF samples in animals that received the oral vaccine, while a strong correlation was observed in other groups. In the present study, evidence points to the effectiveness of the oral vaccine developed for controlling M. hyopneumoniae in pig production under field conditions.
Keywords: animal health; immunology; infectious diseases; respiratory diseases; vaccinology